PKHB1 peptide induces antiviral effects through induction of immunogenic cell death in herpes simplex keratitis - He, Yun; Wang, Chenchen; Liang, Qi; Guo, Rongjie; Jiang, Jiaxuan; Shen, Wenhao; Hu, Kai (Frontiers in Pharmacology, 2022)
Herpes simplex keratitis (HSK) is a severe, infectious corneal disease caused by herpes simplex virus type 1 (HSV-1) infection. The increasing prevalence of acyclovir resistance, the side effects of hormonal drugs, and the ease of recurrence after surgery have made it crucial to develop new methods of treating HSK. HSV-1 evades the host immune response through various mechanisms. Therefore, we explored the role of the immunogenic cell death inducer PKHB1 peptide in HSK. After subconjunctival injection of PKHB1 peptide, we observed the ocular surface lesions and survival of HSK mice and detected the virus levels in tear fluid, corneas, and trigeminal ganglions. We found that PKHB1 peptide reduced HSV-1 levels in the eye and alleviated the severity of HSK. Moreover, it increased the number of corneal infiltrating antigen-presenting cells (APCs), such as macrophages and dendritic cells, and CD8+ T cells in ocular draining lymph nodes. We further observed that PKHB1 peptide promoted the exposure of calreticulin, as well as the release of ATP and high-mobility group box 1 in HSV-1-infected cells in vitro. Our findings suggested that PKHB1 peptide promoted the recruitment and maturation of APCs by inducing the release of large amounts of damage-associated molecular patterns from infected cells. APCs then phagocytized antigenic materials and translocated to the lymph nodes, triggering a cytotoxic T lymphocyte-dependent immune response that ultimately alleviated HSK.